Comparative metagenomics analysis of the rhizosphere microbiota influence on Radix Angelica sinensis in different growth soil environments in China - YAN,Hui (2021)
Abstract We studied the correlation between the soil microbial status and the crop yield or medicinal properties of Angelica s.. Soil from different counties of China were collected and used in this study. Readfq, SOAP denovo, MetaGeneMark, and DIAMOND Resistance Gene Identifier (RGI) software were used in the analysis. A total of 131,345 genes of high quality were obtained, with the number of genes in all samples ranging from 483-42,545 and the average length ranging from 354.88-523.47. The acidobacteria in the non-sterilized group were significantly increased by comparing with the sterilized group, while actinobacteria in the non-sterilized group were significantly reduced by comparing with the sterilized group. There was a strong correlation between the two groups of the planting group and the two groups of the non-planting group, while the correlation between the planting and non-planting group was very weak. There were significant differences in the soil microbial community structure between Min county and Yunnan, as well as significant differences between the dominant genera of Min county and Yunnan. In summary, our study showed that the soil microbial flora in different areas affected the characteristics of Angelica s. roots, while sterilized soil was not conducive to the growth of Angelica s.